Chronic Respiratory Diseases: A Mediterranean View - Masri, Nadine Al; Saadeddine, Rawan; Atallah, Helena; Salameh, Pascale (Information Research Communications, 2025)
Background Understanding Chronic Respiratory Diseases (CRDs) in the Mediterranean region is important for developing effective interventions and policies. Methodology To achieve this, we mapped and quantified CRD research output using a bibliometric study. Utilizing SCOPUS and PubMed databases, we selected a total of 6,686 publications over a 25-year period across 22 countries in the Mediterranean region. We refined our search across databases by using terms such as “Chronic Respiratory Diseases”, “Risk Factors”, and “Management”. VOSviewer aided our analysis in highlighting research collaborations, identifying key content areas, and analyzing the research output distribution by country and institution. Results This analysis showed that, remarkably, the Mediterranean region accounted for a significant 34.7% of global CRD research, indicating its substantial contribution to the field. This substantial contribution has been achieved by key authors such as Miravitlles, Roche, and Soriano. However, our analysis revealed a noteworthy trend, with terms like 'smoker' dominating the discourse, while topics such as allergies and pollutants received comparatively less significance. Conclusion This bibliometric analysis provides valuable insights into the research landscape of CRDs in the Mediterranean area. By identifying research gaps and highlighting areas of focus, we can better direct future efforts towards addressing these pressing health concerns. Moreover, the significant contribution of the Mediterranean region to CRD research emphasizes the importance of encouraging international cooperation. By collaborating across various organizations and nations, we can develop practical strategies for managing and preventing chronic respiratory illnesses, ultimately improving the health outcomes of populations in the Mediterranean region and beyond.
Keywords: Chronic Respiratory Disease; Bibliometric Analysis; Mediterranean; Asthma; Risk Factors; Management.